Developing a Conceptual Model to Sustain Handloom Silk Industry at Sualkuchi, Assam, India - Jain, Jayant; Ratan, Alok (European Journal of Sustainable Development, 2017)
Silk industry in Assam, India is centered at Saulkuchi, Kamrup district. Silk is the protein fiber produced by silkworm for spinning the cocoon. Assam produces three indigenous varieties of silk - Muga, Pat and Eri. The objective of our study is to prescribe a conceptual model using the concepts of distributed economics and sustainability to preserve the unique culture of the area which is diminishing due to lack of the product’s demand. The contextual inquiry was carried out for various stakeholders of Assam silk industry at Saulkuchi - cocoon cultivator, weaver and shopkeeper with an objective to understand the channel of material from raw material to the final product, to understand how they use different tools to perform their tasks and to understand their networking among various stakeholders involved in silk handloom sector. Their responses were analyzed and the stakeholder’s goals, needs and frustrations were identified using AEIOU and empathy mapping. The major frustration of the stakeholders was the decrease in the demand for their products due to the growth of power loom and not able to reach the elite target population. The prescriptions for a village tourism and an e-commerce platform for selling silk handloom fabrics to targeted buyers was built on the concepts of distributed economics and three pillars of sustainability - environment, economic and social. Keywords: Silk, Assam, Distributed Economics, Sustainability, Tourism, E-commerce, Small-scale production units